TYPE OF ALIMENTATION IN THE FIRST YEAR OF LIFE AND FUTURE DEVELOPMENT OF LANGUAGE - Georgeta Burlea; Roxana Milic (Romanian Dental Association for Education, 2013)
Programs of total parenteral nutrition (TPN) or constant debit enteral nutrition (CDEN) will have a positive impact on the health condition and a negative impact on the apparition and future development of language. The identification of any perturbation on the child development triggers the prompt adoption of adequate measures of amelioration and multifactorial support in a multidisciplinary team: doctors, speech therapists, psychologists, kynetotherapists from the Helicomed Medical Clinic Iasi, have put together a program which had as main objectives: the identification of the effects of parental nutrition programs on the future child development; the prevention of apparition of malfunctions in the child development through family counseling and early intervention; the creation of a complex of services addressed to families with children nourished par/entaraly The beneficiaries of this program were a number of 40 children, born prematurely and fed enteraly, who needed numerous admissions in the gastroenterology clinics of intensive care units of "Sf. Maria" children's emergency hospital Iasi.